Storyworlds: ali, hassan and the donkey - Zaidan, Samira R.; Woods, Rosemary (Heinemann UK, 1997)
In a desolate, mist-covered desert, Ali, Hassan, and their loyal donkey set out on a perilous journey to find a legendary oasis. Struggling to navigate through the thick fog, they confront mysterious forces and learn that the mist may be hiding more than just the landscape$1 (Bit holds ancient secrets. As their bond is tested, they must face their fears and uncover the truth behind the mist to survive.s